Processos avaliativos reflexivos integrados a tarefas contínuas no âmbito do ensino superior em física - Pastorio, Dioni Paulo (2018)
At the present work, we developed a series of educational activities aimed to provide a steady rate of study for a course of Physics in the higher education context, which was conceived in a research stage conducted within the Educational Design Research (EDR). This conception of research has as main feature the development of a scientific investigation with the actual routing of a possible solution to a problem, which is, in this case, linked to the process of teaching and learning, identified in a real environment. The chosen problem is the difficulty faced by students to study continuously for the course of Physics I. Based on previous work, we realize that the application of a series of computational activities contributed to the development of skills associated to a numerical computing environment, when students used to develop activities with those characteristics. Thus, the referred solution to this problem is the development of a series of evaluative learning activities, which should be reflective and training ones, providing for the students a pace of constant study throughout the course. These series are based on the premise of the inverted classroom, and educational activities that make it up are developed on the teaching strategy of Troubleshooting. The developed evaluation activities are divided in four different groups: (i) introductory activities, (ii) online/home tests, (iii) classroom tests and (iv) final tests. For the development of this research, we took two technological tools that help both teachers and students: (i) an automatic correction software for solving handmade problems with pencil and paper, and, (ii) an online plataform called GXQ, where are placed and developed extra class activities by students. The presented results by a test in three engineering classes at a public university, to date, shows that the teaching series fulfills its initial objective of promoting a study rhythm. From the analysis of the final questionnaire, we perceived that the students realized that the development of activities with different characteristics favors the continious study of the course subjects, and also a more suitable evaluation process.